Cross-cultural adaptation and validation of the instrument Diabetes - 39 (D-39): brazilian version for type 2 diabetes mellitus patients - stage 1 Adaptación cultural y validación del instrumento Diabetes - 39 (D-39): versión para brasileños con diabetes mellitus tipo 2-fase 1 Adaptação cultural e validação do instrumento Diabetes - 39 (D-39): versão para brasileiros com diabetes mellitus tipo 2 - fase 1 - Flávia Alline de Queiroz; Ana Emilia Pace; Claudia Benedita dos Santos (Universidade de São Paulo, 2009)
The study aimed to accomplish a cross-cultural adaptation of the "Diabetes - 39 - D-39" instrument for Brazil, to test the validity of the adapted version in a sample of type 2 diabetes mellitus patients and to describe the participants of the study, according to the scores obtained on the Likert-type scale. The instrument adaptation process followed several steps: instrument translation; achievement of the consensus in Portuguese; evaluation by an expert committee; back-translation; achievement of the consensus in English; comparison of the original and consensus versions in English; semantic analysis and pre-test of the Portuguese version. Results showed that the instrument items, in the first stage of cultural adaptation to Portuguese, presented high internal consistency levels. Este estudio tuvo como objetivos adaptar, culturalmente, para el Brasil el "Diabetes - 39 - D-39", comprobar la validez de la versión adaptada, en una muestra de personas con diabetes mellitus tipo 2, y describir los participantes del estudio, según los puntajes obtenidos por medio de la aplicación de la escala tipo Likert. El proceso de adaptación del instrumento siguió las siguientes etapas: traducción del instrumento, obtención del consenso en portugués, evaluación por un comité de jueces, back-translation, obtención del consenso en inglés, comparación de las versiones originales y consenso en inglés, análisis semántica y prueba piloto de las versiones en portugués. Los resultados mostraron que el instrumento, en su primera fase de adaptación cultural para el portugués, presentó índices elevados de consistencia interna de sus ítems. Este estudo teve como objetivos adaptar, culturalmente, para o Brasil o "Diabetes - 39 - D-39", testar a validade da versão adaptada, em uma amostra de pessoas com diabetes mellitus tipo 2, e descrever os participantes do estudo, segundo os escores obtidos por meio da aplicação da escala tipo Likert. O processo de adaptação do instrumento seguiu as seguintes etapas: tradução do instrumento, obtenção do consenso em português, avaliação por um comitê de juízes, back-translation, obtenção do consenso em inglês, comparação das versões originais e consenso em inglês, análise semântica e pré-teste das versões em português. Os resultados mostraram que o instrumento, em sua primeira fase de adaptação cultural para o português, apresentou índices elevados de consistência interna dos seus itens.